Reductive degradation of Tetracobalt cluster complexes with a facial C8H8 ligand - synthesis of (Co3(CO)3([my]3-CO)3([my]3-C8H8))- and (Ru(C5Me5)Co3(CO)3([my]3-CO)3([my]3-C8H8)) - Wadepohl, Hubert; Gebert, Stefan; Merkel, Rüdiger; Pritzkow, Hans (European journal of inorganic chemistry, 2000)
Chemical reduction of the cluster complexes [Co4(CO)3(μ3-CO)3(μ3-C8H8)L2] 3 (L2 = C8H8), 4 (L = CO), 5 (L2 = C6H8) and 6 (L2 = 6,6-Ph2C6H4) gives the trinuclear anion [Co3(CO)3(μ2-CO)3(μ3-C8H8)]- (7) in high yield. It is proposed that formation of 7 occurs via degradation of the radical anions [3]- - [6]-, which can be generated reversibly via cyclic voltammetry. The anion 7 is stabilised by the facial C8H8 ligand and does not degrade further. Reaction of 7 with [(C5Me5)Ru(NCMe)3][BF4] results in the formation of [Ru(C5Me5)Co3(CO)3(μ3-CO)3(μ3-C8H8)] (8). The crystal structures of [NEt4]+-7, [(C5H5)2Co]+-7, and 8 were determined. In 7 and 8, the cyclooctatetraene ligand is coordinated to the Co3 face of the cluster in the facial mode.
Gesehen am 25.01.2019
Im Titel sind die Zahlen 3, 5 und 8 tiefgestellt
Im Titel ist [μ] als griechischer Buchstabe dargestellt